U.S. investments in the Latin American economy - United States Department of Commerce; Pizer, Samuel; Cutler, Frederick; United States. Office of Business Economics (Washington, D.C. : United States Department of Commerce, 1976)
This book provides a comprehensive picture of the direct economic contributions of the United States of America companies' operations in the Latin American economy.
Reprint of the 1957 ed. published by the Office of Business Economics, Dept. of Commerce, Washington.
asm 22/01/2019
Loans
Keywords: Investments, American; Investments, Foreign